Analisis Faktor - Faktor Penentu Keberhasilan Proyek Konstruksi Berdasarkan Mutu, Biaya dan Waktu - Silalahi, Yunika Indriani; Masthura, Lely; Fahriana, Nina (Universitas Ibn Khaldun, 2023)
The growth of human needs is closely related to construction projects. Construction projects must be handled professionally and with quality management to achieve what you want. This development allowed the emergence of obstacles during project implementation. This research aims to determine the quality, time, and cost factors that determine the success of a construction project. The questionnaire for this study was administered to 31 people directly involved in the project. The analysis used in this study uses the ranking analysis of the most dominant average/mean value. The results of the analysis show that the most dominant factor influencing the success of a construction project is an accurate price estimate with a mean value of 3.61. Based on the quality is administrative documentation with a mean value of 3.45, and the expertise of the operator of each equipment with a mean value of 3.45. based on time is the Schedule plan with a mean value of 3.77. Analysis of the relationship/correlation between cost, quality and time on the success factors of construction projects shows that the magnitude of the correlation coefficient (r) between cost and quality is 0.534, with a significance or probability of 0.002, cost and time of 0.436. which has a significance or probability of 0.001 and time and quality of 0.532 which has a significance or probability of 0.049.